Has Globalisation Unburdened the Translator? - Zethsen, Karen (Meta, 2010)
In an age where globalisation has become an everyday word it is quite natural to assume that the task of the translator has become much less complicated. As people around the globe increasingly buy the same standardised products, are entertained by the same American films and listen to the same music, it is often taken for granted that generally they have the same frame of reference, that they share a cultura franca. If this is so, translation should indeed be more straightforward as cultural concepts will have a ready name in each language. It would be nonsensical to argue that no global culture exists, but it seems relevant to ask whether the global culture is the only culture or whether it is only a fragment of the cultural framework of a person. This article aims at discussing and defining the concept of cultura franca and whether globalisation has in fact unburdened the translator.